Analisis Faktor-Faktor yang Mempengaruhi Minat Belajar Matematika Siswa Kelas XII SMA Negeri 1 Kejayan - Aini, Ika Nurul; Lestari, Andika Setyo Budi; Khoiri, Miftahul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Not all students have the same interest in learning, and not all areas of knowledge are of interest to students. There are various factors that influence the level of student interest in learning certain subjects at school. This research aims to find out what factors influence students' interest in learning mathematics and how big their influence is. This research uses quantitative research with descriptive statistical analysis methods. The research data source was obtained from class XII-7 students at SMA Negeri 1 Kejayan. Based on data analysis, the factors that influence students' interest in learning include: External factors with indicators including: learning process with an influence level of 67%; friendship circle with an influence level of 49%; infrastructure with an influence level of 42%; and parental support with an influence level of 36%. Internal factors with indicators include: motivation with an influence level of 52%; enjoyment of learning with an influence level of 44%; curiosity with an influence level of 37%; and self-confidence with an influence level of 33%.